解析

微分方程式

微分方程式
\[
\frac{{\rm d} y}{{\rm d} x} = y (1 – y)
\]
を、初期条件\(y(0) = \frac{1}{2}\)の下で解け。

\[\begin{align}
\frac{{\rm d} y}{{\rm d} x} &= y (1 – y) \\
\frac{{\rm d} y}{y (1 – y)} &= {\rm d} x \\
\left(\frac{1}{y} + \frac{1}{1 – y}\right){\rm d}y &= {\rm d} x \\
\log y – \log(1 – y) &= x + C \\
\log\frac{y}{1 – y} &= x + C
\end{align}\]
ここに、\(C\)は積分定数である。初期条件\(y(0)=\frac{1}{2}\)から\(C = 0\)と分かるので
\[\begin{align}
\log\frac{y}{1 – y} &= x \\
\frac{y}{1 – y} &= {\rm e}^x \\
\frac{1 – y}{y} &= {\rm e}^{-x} \\
\frac{1}{y} – 1 &= {\rm e}^{- x} \\
y &= \frac{1}{1 + {\rm e}^{-x}}
\end{align}\]
と求まる。